DEVELOPMENT STRATEGY FOR HALAL CENTER IN UNIVERSITY: A TECHNICAL RECOMMENDATION - Hidayat, Rahmat; Zulham, Zulham; Ramadi, Bagus (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
The Indonesian government encourages universities to actively participate in the halal ecosystem in Indonesia. Currently, many universities have established The Halal Product Process Assistance Agency (LP3H) and The Halal Inspection Agency (LPH) in halal product assurance programs. State Islamic University of North Sumatera (UINSU), which has established LPH and has now changed its name to Halal Center, has not shown significant progress. This research aims to determine the condition of UINSU Halal Center and provide technical recommendations for developing Halal Center and can become a blueprint for other universities that will establish Halal Center. The type of research used in this research is descriptive qualitative research using Institutional Analysis and Development (IAD). This research found several Halal Center problems and their causes. The data was benchmarked against the condition of Sunan Gunung Djati State Islamic University (UIN SGD) Halal Center. The research results provide technical recommendations for developing Halal Center. The recommended concepts are support system, build system, and implementation. The support system is provided by the university leadership, the development system is carried out by the management for the institution's existence, implementation by providing services, assistance and community outreach.